Gluten-free diet or alternative therapy: a survey on what parents of celiac children want. (August 2015) - Norsa, Lorenzo; Tomba, Carolina; Agostoni, Carlo; Branchi, Federica; Bardella, Maria Teresa; Roncoroni, Leda; Conte, Dario; Elli, Luca
Abstract Objectives: Celiac disease (CD) is treated by life-long gluten-free diet (GFD). Novel therapies are under development. Willingness of CD children's parents to alternative therapies and GFD impact were evaluated. Methods: Parents of celiac children on GFD were investigated on need and preference for novel CD therapies, children's enrolment in trials, compliance to and personal judgment on GFD, health status (HS) and quality of life (QoL). Results: About 59.5% surveyed parents expressed the need for alternative therapies with a preference for vaccine-based strategy (39.9%). About 37.7% would accept enrollment in an ad hoc trial, 20.3% would agree to endoscopy during the trial. GFD compliance was 97.4% and well accepted by 93.8%. HS and QoL significantly improved during GFD (p < 0.001). Conclusions: The introduction of novel therapies for CD is desirable for over half of parents, with preference for vaccines. Parents frown upon enrolment in new clinical trials and the subsequent need for additional endoscopy.